How to integrate sustainability in the restaurant business: a case study of the first zero-waste Portuguese restaurant - Figueiredo, Joana Oliveira (2021)
Sustainability is increasingly discussed in a business world that is now also focused on the social and environmental well-being, beyond merely seeking profits. Notwithstanding, the global ecosystem is based on a linear throughput flow of materials, leading to an increase in waste, generating social, environmental, and economic problems. Although the restaurant business has a big contribution to degradation of the environment and social issues, it can also be an important voice in raising consciousness about sustainability and a powerful motivator to the adoption of sustainable practices. However, this is easier said than done. This research aimed to investigate and better understand the integration of sustainability in a restaurant, having in consideration the various stakeholders of the business and their relationships, and bearing in mind the social, environmental, and economic dimensions. The results are based on a qualitative analysis of a case study - Kitchen Dates, the first zero-waste Portuguese restaurant - and interviews were conducted with its stakeholders. The findings reveal that to successfully incorporate sustainability in a restaurant, an integrated and holistic approach is required, that considers all dimensions of sustainability, including a multi-stakeholder perspective based on human relations in every activity of the business. Theoretically, this study introduces a holistic perspective of how to incorporate sustainability in a restaurant, based on the insights of different stakeholders; and from a practical perspective, it is hoped that this dissertation can provide restaurant managers and other industry stakeholders with some guidelines and inspiration for incorporating sustainability in the restaurant business.